Identifying Appropriate Delivery of and Referral to Pulmonary Rehabilitation in Uganda: A Survey Study of People Living with Chronic Respiratory Disease and Health Care Workers - Katagira, Winceslaus; Ndagire, Pauline; Nanyonga, Jaliah; Kasiita, Richard; Kasolo, Josephine N.; Kirenga, Bruce; Singh, Sally J. (International journal of chronic obstructive pulmonary disease, 2021)
Pulmonary rehabilitation (PR) is a low cost, high impact intervention that ameliorates the disability associated with chronic respiratory diseases (CRD). PR is becoming increasingly recognized in low resource settings where the burden of CRD is rapidly increasing. To aid the implementation of PR in Uganda, we conducted a study to assess the attitudes and opinions towards PR among patients with CRD in Uganda and explore barriers faced by health care workers (HCWs) in referring to PR. A cross-sectional study comprising two survey populations: people living with CRD and HCWs regarded as potential PR referrers and PR deliverers. This exploratory study sought initial opinions and thoughts regarding PR, as well as baseline knowledge and potential barriers faced in the referral process. Overall, 30 HCWs (53% female, 43% doctors) and 51 adults with CRD (63% female) participated in the survey. Among those with CRD, the majority reported breathlessness as a major problem (86%) and breathlessness affected their ability to do paid and unpaid work (70%). Interest in PR was high amongst adults with CRD (92%) with preference for a hospital-based programme (67%) as opposed to community-based (16%) or home-based (17%). All HCWs considered PR important in lung disease management, but 77% do not refer patients due to a lack of information about PR. HCWs’ free-text responses identified the need for training in PR, patient education and streamlining the referral process as key elements to develop successful PR referral services. To successfully set up a PR service for people with CRD in Uganda, there is a great need for appropriately tailored training and education of prospective referrers about CRD and PR programs. Educating patients about the benefits of PR as well as streamlining the referral process is critical in expanding PR services across Uganda to fulfill this unmet need.
Keywords: respiratory rehabilitation, chronic chest symptoms, medical workers, enthusiasm, knowledge, training